Clinical Experience of Use of Percutaneous Continuous Nervemonitoring in Robotic Bilateral Axillo-Breast Thyroid Surgery - Zhang, Daqi; Wang, Cheng; Wang, Tie; Du, Rui; Li, Kunlin; Yang, Mingyu; Xue, Gaofeng; Dionigi, Gianlorenzo; Sun, Hui (Frontiers in Endocrinology, 2022)
Introduction and Objective. There is a need for a simplified technique for C-IONM in robotic surgery. The primary aim of this study was to describe our clinical experience with the use of percutaneous C-IONM in robotic bilateral axillary thyroid surgery. Methods. This study prospectively enrolled 304 consecutive patients who underwent robotic thyroidectomy via the bilateral axillo-breast approach and standardized C-IONM via percutaneous probe stimulation. Results. 323 RLNs were analyzed. C-IONM with percutaneous probes was feasible in all cases. During this study, we did not record any cases of probe displacement, and no additional robotic maneuvers were required. The average stimulation intensity was 2 mA. There were no adverse local or systemic C-IONM side effects. The mean time required for probe positioning was 3 minutes. The EMG amplitude signal of 48 RLNs decreased significantly, < 50% from the original V1 signal. In these cases, the surgical procedure was modified. Conclusion. The proposed percutaneous C-IONM provides a simplification of the continuous monitoring procedure for robotics. The advantage of percutaneous C-IONM is that it does not require additional trocar space, repeated instrument changes, and unmodified cosmesis. To our knowledge, this is the first study on the application of percutaneous C-IONM in robotic thyroid surgery.